Modelling of reactive distillation column by using mosaic - Chieng, Tiew Hing (2014)
Due to many advantages of reactive distillation column (RD) comparing to traditional method (reactors follows by distillation columns) in chemical synthesis, RD has been drawing attentions of researchers around the world to explore its potentials in chemical industries. Modelling of RD can be made by many different modelling environments such as Matlab, Fortran and so on. However, it is a time consuming process and a lot of effort will be required in order to get the solutions of the model. Since the modelling is done by using their own programming languages, it has the poor readability. Thus, users prone to make the mistakes during coding and error identification will be difficult by using these modelling software. In this study of RD modelling, a new modelling environment called MOSAIC will become the focus. MOSAIC is a web based modelling software and it introduces the new modelling approach in order to overcome what it seems as insufficient places of other modelling software. The key features of MOSAIC include modelling in the documentation level, reuse of model elements, code generation for other modelling environments and centralized cooperation on internet. (Kuntsche, Barz, Kraus, Arellano-Garcia, & Wozny, 2011) Modelling of reactive distillation column is based on the steady state equilibrium model. It is assumed that the liquid and vapour phase behave ideally. Steady state equilibrium model can be described by MESH equations. MESH equations are material balance equation, phase equilibrium equation, summation equations and energy balance equation. From the results, it can be seen that almost 100% conversion of reactants are achieved with 94% of MTBE purity. The temperature profile shows that the temperature is maintaining at 354Kfrom condenser to feed stage. This is due to high purity of n-butene in each stages. After feed stage, the temperature increases rapidly until it reaches highest temperature of 424K at reboiler stage. This is caused by high mole fraction of MTBE from condenser to reboiler stage. MOSAIC makes the modelling possible even without the knowledge of programming language. Latex documentary language is used by MOSAIC in documentation of modelling equations. High readability of Latex allows modelling using MOSAICto beless errors and without much effort